2015
DOI: 10.26719/2015.21.9.621
|View full text |Cite
|
Sign up to set email alerts
|

Self-management practices among type 2 diabetes patients attending primary health-care centres in Medina, Saudi Arabia

Abstract: The purpose of this study was to estimate the frequency of self-management activities among people who have type 2 diabetes in Saudi Arabia. The Arabic version of the Summary of Diabetes Self-care Activities questionnaire was used to identify self-management practices among 210 patients with type 2 diabetes mellitus. Only 15% of participants had a blood glucose level indicative of good glycaemic control (glycosylated haemoglobin ≤ 7 mmol/L). Most reported that they took their medication as prescribed, but many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
54
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 17 publications
13
54
4
2
Order By: Relevance
“…This study found no association between age with self-care, and similar findings have been reported by other studies [3538]. Age was not associated with self-efficacy, depression and diabetes distress in this study.…”
Section: Discussionsupporting
confidence: 91%
“…This study found no association between age with self-care, and similar findings have been reported by other studies [3538]. Age was not associated with self-efficacy, depression and diabetes distress in this study.…”
Section: Discussionsupporting
confidence: 91%
“…8 Other factors that determine diabetes self-care behaviors include diabetes education, duration of disease, presence of comorbid conditions, body mass index (BMI), foot care, and smoking. 9 A recent study in Madinah by Al Johani et al 10 reported that only 15% of the participants had good glycemic control, 29% of participants were incapable of managing their diet, 47% did not exercise regularly, 85% did not monitor their blood glucose regularly, 41% were careless in their foot care, and 25% had poor compliance for their prescribed medication. They concluded that there is a tremendous scope to improve DM self-care practices in Saudi Arabia and increase the proportion of patients who achieve good glycemic control.…”
mentioning
confidence: 99%
“…Sample size calculation. In reference to the study of Al-Johani et al, 10 entitled "Self-management practices among type 2 diabetes patients attending primary health-care centres in Medina, Saudi Arabia" which reported a prevalence of poor self-care behavior of 29%. This prevalence was applied to find the optimal sample size.…”
mentioning
confidence: 99%
“…However, a recent clinical audit conducted across UNRWA's operational fields identified weaknesses in lifestyle counselling and limited evidence of self-management of NCDs (32). Consistently, self-management of diabetes in Jordan and Saudi Arabia is a particular problem (33,34). In Saudi Arabia, it is constrained by the exclusion of glucometers from patients' benefits packages (34).…”
Section: Self-management Supportmentioning
confidence: 99%
“…Consistently, self-management of diabetes in Jordan and Saudi Arabia is a particular problem (33,34). In Saudi Arabia, it is constrained by the exclusion of glucometers from patients' benefits packages (34). The same exclusion applies to UNRWA because of budget limitations.…”
Section: Self-management Supportmentioning
confidence: 99%